2016
DOI: 10.1002/jctb.5133
|View full text |Cite
|
Sign up to set email alerts
|

UV‐C‐driven oxidation of ciprofloxacin in conventionally treated urban wastewater: degradation kinetics, ecotoxicity and phytotoxicity assessment and inactivation of ciprofloxacin‐resistant Escherichia coli

Abstract: BACKGROUND This study aims at evaluating the degradation of the antibiotic ciprofloxacin (CIP) in urban wastewater effluents using a UV‐C‐driven oxidation processes in the presence of hydrogen peroxide. Under the optimum experimental conditions, the phytotoxicity and ecotoxicity of the treated samples were investigated against one plant species (Sinapis alba) and a crustacean (Daphnia magna), respectively. The efficiency of the process to remove E. coli and ciprofloxacin‐resistant E. coli was also assessed. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
(125 reference statements)
1
8
0
Order By: Relevance
“…In addition, the band gaps of Co 3 (PO 4 ) 2 and Ag 3 PO 4 are 4.40 and 2.33 eV respectively as calculated by UV-visible DRS. The potential of the CB can be calculated via Eqn(8). Hence we deduced that the E CB values of Co 3 (PO 4 ) 2 and Ag 3 PO 4 were −0.37 and 0.30 eV respectively.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, the band gaps of Co 3 (PO 4 ) 2 and Ag 3 PO 4 are 4.40 and 2.33 eV respectively as calculated by UV-visible DRS. The potential of the CB can be calculated via Eqn(8). Hence we deduced that the E CB values of Co 3 (PO 4 ) 2 and Ag 3 PO 4 were −0.37 and 0.30 eV respectively.…”
mentioning
confidence: 90%
“…For example, ofloxacin (OFX) is a frequently detected FQ antibiotic in various environmental samples such as wastewater treatment plant effluents, sea waters and surface waters in concentrations ranging from ng L −1 to µg L −1 . Previous studies demonstrated that FQs were subject to degradation in aqueous systems, mineralization of these compounds is often incomplete and many of the organic products identified retain the core quinolone ring structure, which is essential to FQs' antibacterial activities . The quantitative efficacy of various treatment processes for removing antibacterial activity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations